PEMBENTUKAN STRATEGI MELALUI AUDIO KOMUNIKASI DALAM APLIKASI GAME FPS(VALORANT) - Ahmad Muzakki; Ahmad Hasyeimi Syariati; Kholdi Darussalam; Fathiyah Nopriyani (Djtechno: Jurnal Teknologi Informasi, 2024)
This research discusses the influence of online games, especially the FPS game Valorant, in daily life and PC application development. Valorant is a popular FPS game and has active users in Indonesia. This game offers uniqueness with agent characters who have special skills. Although the Valorant game can make players addicted, this game also provides opportunities to make money and achievements in the world of e-sports. Strategy is also an important factor in the Valorant game, including selecting equipment purchasing items. Communication is also an important aspect in this game, with an audio communication feature that makes it easier for players to communicate and plan strategies. This research uses the UX Research method to understand user experience and analyze the data obtained.